Studi Komparatif Pendapatan Dan Efisiensi Usaha Dagang Baju (Studi Kasus Pedagang Baju Bali Menetap Dan Semi Menetap Di Daerah Kuta) - Mariani, Ni Komang; Saskara, Ida Ayu Nyoman (E-Jurnal Ekonomi Pembangunan Universitas Udayana, 2016)
The island of Bali is famous tourist area that is visited by many tourist. Kuta District is the center of local and foreign tourists destination. The public saw the opportunity to open a trading business that focuses on selling the needs of travelers, especially Bali clothes. There are seventy-seven merchant clothes Bali sampled in the study. Traders clothes Bali is divided into two places that sell services to merchants settled fifty and twenty-seven for the semi-sedentary traders. This study aims to determine the level of income and the level of efficiency of trading business Baju Bali between traders settled and semi settled. The analysis tool used is descriptive and comparative statistics that the t test. The main reason traders choose to trade a service that is of terms of lease of land, the legality of the business license of the Village People and comfort level. Income traders settled Rp 7,937,917.67 higher than the income trader settled semi Rp 4,759,583.35. The level of efficiency traders settled 1.70 less than the level of efficiency semi traders settled 1.82. On two different test statistics show that the average real difference between income traders settled and semi settled merchants.
Keywords: Revenue, Efficiency, bali clothes trader